2017
DOI: 10.1007/s00170-017-0273-6
|View full text |Cite
|
Sign up to set email alerts
|

A review of univariate and multivariate process capability indices

Abstract: This paper oers a review of univariate and multivariate Process Capability Indices (PCIs). PCIs are used in the industry to quantify how well a process can meet customer requirements. Univariate PCIs describe the capability of one single product characteristic. Multivariate PCIs deal with the multivariate case in which the measures of all multiple product characteristics must be within specication limits to be conforming. When analyzing the capability of processes, decision makers of the industry may choose on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 67 publications
0
25
0
1
Order By: Relevance
“…Whereas, the third component LI takes a value of 0 or 1 [18]. Furthermore, a recent review of multivariate and univariate process capability indices is provided in [23].…”
Section: Process Capabilitymentioning
confidence: 99%
“…Whereas, the third component LI takes a value of 0 or 1 [18]. Furthermore, a recent review of multivariate and univariate process capability indices is provided in [23].…”
Section: Process Capabilitymentioning
confidence: 99%
“…The paper must be written In today's competitive and globalized markets, industries are obligated to produce high-quality and cost-effective products that consistently meet the consumers and engineering design specifications (Felipe & Benedito, 2017;Goswami & Dutta, 2013;Krolczyk et al, 2015). Subsequently, quality level and process capability have become indispensable attributes and key issues among producers to achieve competitive advantage particularly in the world of knowledgeable consumers (Krolczyk et al, 2015;Leiva, Marchant, Saulo, Aslam, & Rojas, 2014;Lupo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed and somewhat critical review on PCIs is available in Kotz and Lovelace, 3 whereas Vännman 4 proposes a unified approach. A thorough review of contributions is reported in de‐Felipe and Benedito 5 and Bong‐Jin and Kwan‐Woo 6 among others). Most of the papers focus on the assumption of normality of the random components, but how capability indices could be efficiently estimated when non normal distributions are involved remains a challenge.…”
Section: Introductionmentioning
confidence: 99%